Pengembangan Kompetensi Profesional Guru Melalui Pelatihan Berbasis Nilai-Nilai Islam - Titi Oktarina Sambadha; Ida Fitri; Tati Lasmita; Indra Mukti Abam; Kasinyo Harto; Febriyanti Febriyanti (Journal of Islamic Education, 2026)
This study aims to analyze the concept of teacher professional competency development through Islamic values-based training within the perspective of human resource management in Islamic education. Using a qualitative approach with library research design, data were obtained from primary sources including the Quran, hadith, and works of Islamic educational thinkers, as well as secondary sources comprising scientific journals, books, and relevant policy documents. Analysis was conducted through content analysis and comparative analysis of selected literature. The findings indicate that teacher professional competency in the Islamic perspective encompasses the integration of spiritual, pedagogical, and moral dimensions that are inseparable. Effective training programs are designed based on the concepts of tarbiyah, ta'lim, and ta'dib by integrating classical Islamic methods with modern learning approaches. Implementation success is significantly influenced by madrasah principal leadership, Islamic organizational culture, and teachers' intrinsic motivation as waratsatul anbiya. Key obstacles include budget limitations, heavy workload, and resistance from some senior teachers. The study concludes that Islamic values-based training is proven capable of enhancing professional competency while simultaneously strengthening teachers' spiritual identity in a holistic and sustainable manner.